A social science‐inspired complexity policy: Beyond the mantra of incentivization. Issue 6 (7th April 2014) - Squazzoni, Flaminio; Gilbert, Nigel; Bullock, Seth
<x xml:space="preserve">Abstract</x> This study suggests that cross‐fertilization between complexity and social science could provide a new rationale for policy. We look at the weakness of conventional policy thinking and excessive faith in incentives and the underestimation of social interaction on individual choices. Recent examples of experimental and computational research on social interaction indicate the importance of understanding preexisting social norms and network structures for targeting appropriately contextualized policies. This would allow us to conceive policy not as something that takes place "off‐line" outside systems but as a constitutive process interacting with self‐organized system behavior. This article aims to pave the way for a complexity‐friendly policy that allows us to understand and manage more than predict and control top‐down. © 2014 Wiley Periodicals, Inc. Complexity 19: 5–13, 2014